Tela’ah Buku Ajar Al-Balaghah Al-Wadhihah (Karya ‘Ali Al-Jarim Dan Musthafa Amin) - Walfajri Walfajri (Institut Agama Islam Negeri Metro, 2019)
This paper aims to assess the book of al-Balaghah al-Wadhihah compiled by ‘Ali al-Jarim and Mustafa Amin as a textbook used in the Department of Arabic Language Teaching at the Education Faculty of State Islamic Istitute of Metro. The study of this textbook uses the literature review method by examining various theories about the principles and criteria for preparing textbooks as an analysis tool. The result of study found that the book of al-Balaghah al-Wadhihah is in accordance with the principles and criteria for the preparation of a good textbook. There are some advantages and disadvantages of this textbook. The advantages of this textbook include: the basic concepts of the subject are simple, containing verses of the Qur'an as an example of discussion of material and practice. However, it still has many disadvantages, among others: this textbook is composed for Arabic (Egyptian) students and uses Arabic as the language of instruction, not compiled for Non-Arabic (Indonesian) students so that it is difficult to understand by Indonesian students who are weak in nahwu-sharaf mastery and lack of vocabulary.